The effect of food and frozen storage on the nutrient cornposition of sorne Mrican fishes - Omotosho, J S (1995)
Specirnens of Tilapia zillii, Clarias lazera, Channa obscura, Synodontis schalt, and Scomberomus tritor were collected between January and Decernber 1990, covering fue dry and rainy seasons. According to stornacl;t analysis fuey were classified as either herbivorous, camivorous, omnivorous, plankton consumers or invertebrate feeders. The crude protein, lipid amd rnoisture contents were determined both for pre- and post frozen storage, with the exception of S. tritor (only post storage data). The percentage of total lipid and protein decreased significantIy after each succeeding frozen storage, and the rnoisture content shows a trend similar to other parameters in all the species. Fresh flsh is of the highest nutritional value. The feeding habit had sorne relationship with the rnuscle protein, fat and rnoisture content